Pisma Wencla Šolarja O. S. B. iz Amerike (1895-1911) - Friš, Darko (Zgodovinski časopis, 1999)
The contribution analyses the correspodence of Benedictine priest Wencel Šolar which originated between 1895 and 1911 in the course of his pastoral work in Pennsylvania and Illinois, USA. The letters are addressed to his relatives in Rudno, a little village in Selška dolina in Upper Carniola, Slovenia. The author was especially interested in Šolar's description of his pastoral work in America, his impressions of his "new homeland" his relationship with other Slovene immigrants and toward immigration as well as Šolar's description of everyday life in America. The original letters are part of the Immigration History Research Center, University of Minnesota archives in St. Paul, Minnesota
Keywords: history of Slovenes; Šolar, Wencel; emigration; history; zgodovina; emigrants; Slovenci; Slovenes; izseljeništvo; USA; izseljenci; american Slovenes; 19th century; ZDA; United States of America; ameriški Slovenci; 19. st.